The sacrifices of the body: Configuration, forms and evolution of the memories of Blas de Lezo in 18th and 19th century Spain - Soriano Muñoz, Nuria; Chillida, Javier Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Based on the methodological and theoretical contributions of memory studies, this article analyses the configuration of the memory of Blas de Lezo from his beginnings to the late 19th century. From the study of biographies, historical compendiums, and mainly journalistic articles, an attempt is made at establishing what the factors that contribute to the construction of memory, the versatility of its political functionality and the constant modifications produced by its public use. The revalorization of Lezo's figure is interpreted as a symbol of the empire and the Spanish nation, the essence of Spanishness - along with the exaltation of the fueros and Basque distinctiveness- and an example of sacrifice for a liberal navy in dark times. From the spreading of his memory in the 18th century there is a shift to a more cohesive narrative, its most algid point being 1870, because of the Basque foralistas and the Spanish military. It is argued that at the end of the century, after the struggle to establish a true narrative of what happened in Cartagena de Indias, the military version of the character triumphs, imposing itself with the Hispanic-American war of 1898 as a symbol of resistance against the enemy.